2010
DOI: 10.1007/s00540-010-0926-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraoperative acetated Ringer’s solution with 1% glucose on glucose and protein metabolism

Abstract: The infusion of a small dose of glucose (1%) during minor otorhinolaryngeal, head and neck surgeries may suppress protein catabolism without hyperglycemia and hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 33 publications
1
33
2
1
Order By: Relevance
“…Blood β-OHB levels correlate with the amount of gluconeogenesis via lipolysis (i.e., fat catabolism). A recent clinical study (16) reported that glucose administration during surgery under sevoflurane anesthesia significantly suppresses lipolysis. Consistent with this finding, blood β-OHB levels decreased after glucose administration in group S-IVGTT in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Blood β-OHB levels correlate with the amount of gluconeogenesis via lipolysis (i.e., fat catabolism). A recent clinical study (16) reported that glucose administration during surgery under sevoflurane anesthesia significantly suppresses lipolysis. Consistent with this finding, blood β-OHB levels decreased after glucose administration in group S-IVGTT in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have shown that the administration of glucose during surgery can inhibit starvation-induced catabolism [1][2][3][4][5][6][7] and attenuate post-operative insulin resistance [8]. Furthermore, the degree of postoperative insulin resistance was found to be an independent factor associated with the length of the postoperative hospital stay [9].…”
Section: Introductionmentioning
confidence: 82%
“…Ketone body fractions increased significantly in both groups until end of surgery because glucose was not administered during surgery. To suppress catabolism, not only preoperative but also intraoperative glucose administration should be considered [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%